Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Levin speaks on behalve of the students from Moscow. Under him: Emma Goldman. Third from the left: Maksimov
Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Levin speaks on behalve of the students from Moscow. Under him: Emma Goldman. Third from the left: Maksimov.